Corrosive Poisoning- A Case report with Literature Review - Gautam Rawal; Nitin Garg; Umar Rasool Wani; Sankalp Yadav (International Journal of Medical Research and Review, 2015)
Corrosive gastrointestinal tract injuries are a source of considerable mortality and morbidity all over the world. Despite this, the actual data on the epidemiology of the poisoning/ingestion are scarce due to lack of well established reporting system for poisoning in most countries. The burden of this poisoning is naturally more in developing countries like India, where the condition is common because of poorly regulated sale of corrosive substances. The authors here present you a case of a young male who had accidental acid ingestion and complications and was managed under them, with review of the management of corrosive ingestion.